(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The paper addresses the topic of a microgrid. form involving decentralized power generation sources connected to three-phase loads exhibiting nonlinearity. The microgrid incorporates distributed generation sources, namely a self-excited induction generator-driven a mini-hydrosystem, battery and the solar PV panels. In the presence of nonlinear load situations, the Unified Power Quality Controller (UPQC) is intended to improve the power quality inside the microgrid system. This UPQC is built on a power electronics component based on a voltage source converter that simultaneously provides current and voltage into the microgrid. This action serves the purposes of eliminating harmonics, compensating reactive power, and regulating voltage. Furthermore, a bidirectional buck-boost controller connects the battery to regulate power flow within the microgrid, accounting for fluctuations in nonlinear load and solar radiation. A boost converter connects the solar photovoltaic (PV) system. The system also includes solar PV generating with MPPT capabilities, a battery supported by a buck-boost converter, and the UPQC. Additional components include a 3.2 kW, 230 V, 50 Hz Self-Excited Induction Generator (SEIG) and solar PV generation. MATLAB software was used to carefully design, develop, and simulate each of these parts.